Basic heat and mass transfer - Mills, Anthony F. (Prentice Hall, 1999)
Offers complete coverage of heat transfer with broad up-to-date coverage that includes an emphasis on engineering relevance and on problem solving. Integrates software to assist the reader in efficiently calculations. Carefully orders material to make book more reader-friendly and accessible. Offers an extensive introduction to heat exchange design to enhance the engineering and design content of course to satisfy ABET requirements. For professionals in engineering fields.